Cybergogy-Based Training for Enhancing Digital Literacy to Support Indonesia’s Golden Generation 2045 at The Aisyiyah Community, Bangkalan Regency - Soeryanto, Soeryanto; Hidayatullah, Rachmad Syarifudin; Cholik, Mochamad; Anwar, Saiful; Susanti, Nur Aini; Ajiban, Mochammad Hildad (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to enhance digital literacy among members of the Aisyiyah Community in Burneh Subdistrict and to support the realization of Indonesia’s Golden Generation 2045. The program was designed to equip participants with knowledge and skills in utilizing digital technology through a cybergogy-based learning approach. The implementation methods included planning, introduction, digital literacy training, collaborative practice, evaluation, and sustainable follow-up. A total of 37 community members participated, representing diverse backgrounds such as homemakers, entrepreneurs, and teachers. Evaluation instruments consisted of a pretest, a posttest, and a questionnaire administered via Google Forms. Statistical analysis revealed a significant difference between pretest and posttest scores (Asymp. Sig. < 0.05). The average N-Gain score of 0.62 (moderate category) indicated an improvement in participants’ understanding. Participant responses were also positive, with an average Likert scale score of 3.25, reflecting tangible benefits from the training. A key success factor was the use of Smart TV media, which enabled facilitators to deliver content more interactively and engagingly. Additionally, the provision of rewards helped boost participant motivation. A follow-up impact of the program was the establishment of a smart classroom at TK ABA 4, serving as a sustainable outcome of the training. Overall, this community service activity effectively enhanced digital skills, learning motivation, and community engagement, while serving as a strategic model for integrating technology into community-based education in the digital era.